Challenges in Adapting Islamic Education Teaching Methods to Students' Learning Styles in the Digital Technology Era - Isnaniah Noviana; Jasiah Jasiah (The Future of Education Journal, 2026)
This article examines the challenges faced by Islamic education teachers in adapting their teaching methods to students' learning styles in the digital technology era. Technological advancements, including the Internet, artificial intelligence (AI), and social media, have transformed the ways students interact, access information, and construct knowledge, making traditional instructional approaches such as lectures and rote memorization increasingly less relevant. This study employed a literature review approach by analyzing academic publications published over the past ten years. The findings reveal several major challenges encountered by Islamic educators, including the mismatch between traditional teaching methods and digital learning needs, limited technological literacy among teachers, the risk of distraction caused by digital content, and the necessity of maintaining the values of the Qur'an and Hadith as the primary foundations of Islamic education. Furthermore, the diversity of students' learning styles visual, auditory, and kinesthetic requires teachers to adopt more creative, flexible, and adaptive instructional strategies supported by appropriate learning technologies. Therefore, Islamic educators need to enhance their digital competencies, promote ethical technology use, and continuously emphasize the cultivation of noble character (akhlaq). With appropriate strategies, Islamic education can remain relevant, contextual, and meaningful while preparing students to become faithful, morally responsible, and capable of meeting the challenges of contemporary society. This study aims to explore the challenges and formulate strategic recommendations for Islamic educators in adapting teaching methods to students' learning styles in the digital era while ensuring that spiritual values are preserved amid rapid technological advancement.